2018
DOI: 10.18388/abp.2018_2612
|View full text |Cite
|
Sign up to set email alerts
|

Impact of polyphenol-rich green tea extracts on the protection of DOPC monolayer against damage caused by ozone induced lipid oxidation

Abstract: Effectiveness of green tea (compared to two single polyphenols) in removing ozone derived reactive oxygen species acting on dioleoylphosphatidylcholine monolayers was determined. Lipid oxidation was followed by changes in mechanical properties of the layer spread on the aqueous subphase containing various amounts of ozone in the presence and absence of polyphenolics. It was shown that the tea extract (containing 8.5 x 10 mg/cm polyphenols) is capable of inactivating 0.4 ppm ozone. The DPPH radical scavenging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The highest TRO value was demonstrated for EGCG‐combined AgNPs. Rudolphi‐Skórska et al (2018) showed that EGCG is more effective than GA in direct protection of the model cell membrane against oxidative stress. TEM imaging indicated that EGCGAgNPs and EGCGGAAgNPs had the highest cell penetration ability.…”
Section: Discussionmentioning
confidence: 99%
“…The highest TRO value was demonstrated for EGCG‐combined AgNPs. Rudolphi‐Skórska et al (2018) showed that EGCG is more effective than GA in direct protection of the model cell membrane against oxidative stress. TEM imaging indicated that EGCGAgNPs and EGCGGAAgNPs had the highest cell penetration ability.…”
Section: Discussionmentioning
confidence: 99%
“…Stress conditions were created by introducing ozone into the buffer, where in the water environment ozone undergoes decomposition reactions forming oxidative radicals, among others hydroxyl radicals and superoxide anion radicals [ 35 ]. The obtained mixture of reactive oxygen species corresponds to those naturally occurring in cells, due to the redox status disturbance imbalance [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Green tea contains a many of polyphenols, especially monomeric avonols [75,76]. Since there are very limited studies for investigating protective effects of green tea polyphenols against particulate pollutants [77,78], we examined green tea avonols rich fraction FLGs and its representative compounds, quercetin, kaempferol, and myricetin for damage attenuation by FDP. Among these compounds, myricetin have shown potent positive effects of cell survival under FDP-stimulation dose-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%